Beneficial response to anakinra and thalidomide in Schnitzler's syndrome. Issue 4 (11th August 2005) - de Koning, H D; Bodar, E J; Simon, A; van der Hilst, J C H; Netea, M G; van der Meer, J W M
Abstract : Background: Schnitzler's syndrome is an inflammatory disorder characterised by chronic urticarial rash and monoclonal gammopathy, accompanied by periodic fever, arthralgia or arthritis, and bone pain. The cause and treatment are still unknown. Objective: To assess treatment with thalidomide and an interleukin 1 receptor antagonist, anakinra, in Schnitzler's syndrome. Case reports: Three patients with Schnitzler's syndrome are described, one with IgM gammopathy, two with IgG type. In one patient, thalidomide induced complete remission, but was stopped because of polyneuropathy. Anakinra 100 mg daily in all three patients led to disappearance of fever and skin lesions within 24 hours. After a follow up of 6–18 months, all patients are free of symptoms. Conclusion: Anakinra proved to be effective in three patients with Schnitzler's syndrome. This treatment is preferable to thalidomide, which induced a complete remission in one of our patients, as it has fewer side effects.